PERCEPTION ON BANK INTEREST AND THE USE OF ISLAMIC BANKS: CASE STUDY INDONESIAN STUDENTS IN MEDINA SAUDI ARABIA - Almagribi, Ahmad Bilal; Possumah, Bayu Taufiq; Husayn, Halimi (AL-QARDH, 2020)
This study aims to investigate the perceptions of Indonesian students in Medina, the Kingdom of Saudi Arabia about bank interest and Islamic banks usage. By using questionnaires data collection method and purposive sampling technique, 40 students have been interviewed online in this study. The data is then analyzed by descriptive percentage. This study found that most Indonesian students in Medina consider bank interest as usury and only 5% of them thought that both were different. The students who consider bank interest as usury argue that the contract between the customer and the bank is a Qordh (loan) contract. In contrast, respondents who consider the bank interest and usury are different, arguing that the interest is not always as usury according to some scholars who do not categorize the contract between bank and customer as Qordh, but as Tamwil (financing). This study also found that most of the students using Islamic banks and at the same time some of them also have conventional accounts for various reasons, such as the limited number of ATMs and branch offices, and no Islamic debit cards yet that are accepted as credit cards in online transactions.